Mediações : dialética e psicanálise na crítica do sujeito na Dialética do esclarecimento de Th. Adorno e Max Horkheimer. - Helder Silva Vilela (2020)
This work analyzes the way Th. Adorno articulates dialectics and psychoanalysis, focusing mainly on the Dialectic of enlightenment, a joint work with Max Horkheimer, aiming to elucidate the position and constitution of individuals in the face of false totality. To this end, initially, the dissertation addresses the theoretical bases that support the dialectical perspective propaedeutic to the review of enlightenment. Then, the examination of the review of enlightenment evidences the living and constitution conditions of individuals immersed, above all, in the harmoniously false dynamics of the cultural industry. Once the dialectical perspective in this block is presented, the psychoanalysis is also peered according to the adornian perspective, aiming to evidencing its collaboration for a critical theory of society and, specifically, in the interpretation of the conditions of individuals adapted to the status quo. Finally, dialectics and psychoanalysis outline the figure of the individual denounced in the Dialectic of enlightenment.